Modernism : - Latham, Sean (New modernisms series, 2015)
Modernism: Evolution of an Idea traces the development of the term "modernism" from cultural debates in the early twentieth century to the dynamic contemporary field of modernist studies. Rather than assuming and recounting the contributions of modernism's chief literary and artistic figures, this book focuses on critical formulations and reception through topics such as: the evolution of modernism from a pejorative term in intellectual arguments to its subsequent centrality to definitions of new art; new criticism and its legacies in the formation of the modernist canon in anthologies, classrooms, and literary histories; and shifting conceptions of modernism during the rise of gender and race studies, French theory, Marxist criticism, postmodernism, and more.